2023
DOI: 10.3390/jcm12072652
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Temporomandibular Disorders (TMD) and Posture Evaluated trough the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD): A Systematic Review with Meta-Analysis

Abstract: Background: Temporomandibular disorders (TMDs) are a series of disorders that affect the muscles and joint. Symptoms include joint pain, muscle pain, and limitation of mouth opening. One of several multifactorial diseases, temporomandibular dysfunction has mostly been linked to five etiological factors: occlusion, trauma, severe pain stimuli, parafunctional activities, and psychological elements, including stress, anxiety, and depression. The position of the human body as it is displayed in space is referred t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 51 publications
(50 reference statements)
1
31
0
Order By: Relevance
“…TMDs are a group of conditions that affect the temporomandibular joint (TMJ) and the surrounding muscles 20,31,32 . The muscular aspect of TMD is particularly important, as it can contribute to pain, dysfunction and limited range of motion 21,33 .…”
Section: Discussionmentioning
confidence: 99%
“…TMDs are a group of conditions that affect the temporomandibular joint (TMJ) and the surrounding muscles 20,31,32 . The muscular aspect of TMD is particularly important, as it can contribute to pain, dysfunction and limited range of motion 21,33 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common clinical manifestations of TMD are pain, joint noises, tenderness, dysfunction and functional limitation in the articular movement; furthermore, TMD patients may also suffer from headaches, earaches, tinnitus, dizziness, posture impairment, and neck and shoulder pain. 3,5,6,48 Indeed, recent evidence showed that TMD could negatively influence quality of life, suggesting a prompt and adequate rehabilitation of TMD pain. 10,12,13,49 Viscosupplementation with HA has been widely used in TMJ pathological changes considering that HA is a glycosaminoglycan naturally found in the synovial fluid.…”
Section: Discussionmentioning
confidence: 99%
“…In order to manage TMD, it is important to reduce stress. 26,27 This can include relaxation techniques, such as deep breathing, yoga and meditation. 26 It is also important to avoid activities that may cause further strain on the TMJ, such as chewing gum, nail-biting and clenching or grinding of the teeth.…”
Section: Introductionmentioning
confidence: 99%